Monsoon Season Rain Prediction for the Year 2015 for Telangana, India Based on Telangana’s Historical Rain Data (The Global Environmental Engineers, 2015)
In this work the prediction of rain is based on average of two methods. In these methods, historical rain data of Telangana from 1981 to 2012 are selected for projection. These methods take into account the trends in rain pattern also. Among the results are the effects of El Nino and La Nina which for Telangana are not as significant as compared to higher frequencies on annual rainfall basis. The period of these combined effects (El Nino and La Nina) is 10.67 years. The average rainfall of Telangana is 70 centimeters (cms). The normal range of rain varies between the mean+standard deviation as per the Indian Meteorological Department (IMD). The forecast is being made in November 2014 for the Year 2015 that the rain will be normal in the month of June whereas some excess rain will take place in later months as shown in Tables 1 to 5 here. The advantage of this approach is that it gives farmers far more time than they get presently when preliminary predictions are announced by Indian Meteorological Department in April for each monsoon.
Keywords: Monsoon rain prediction; annual rainfall; rainfall frequency spectrum; El Nino and La Nina influence on rainfall; drought and famine; crop failure